Multiple myeloma in patients up to 30 years of age: a multicenter retrospective study of 52 cases. Issue 2 (28th January 2019) - Jurczyszyn, Artur; Davila, Julio; Kortüm, K. Martin; Jayabalan, David S.; Vij, Ravi; Fiala, Mark; Milunovic, Vibor; Chim, C.S.; Wiśniewska-Piąty, Katarzyna; Waszczuk-Gajda, Anna; Crusoe, Edvan; Hajek, Roman; et al.
Abstract: A small proportion of patients with multiple myeloma (MM) are diagnosed at a very young age. The clinicopathological characteristics and prognosis of these patients are not well known. This analysis included 52 patients diagnosed with MM at the age of ≤30 years (range: 8–30 years). 68% of patients had International Scoring System (ISS) 1 MM; 22% presented with the light chain-only disease, and 48% with elevated serum lactate dehydrogenase (LDH). 85% of patients were treated with novel agents, and 62% received front-line autologous stem cell transplantation (ASCT). Overall response rate (ORR) to front-line treatment and ASCT were 71% and 90%, respectively. The group was followed-up for the median period of 86 months. The median overall survival (OS) was 166 months (95% CI: 53–222), with 5-year OS rate of 77% (95% CI: 61.0–87.9). This findings suggest that the prognosis in young MM patients may be as good if not better than in the general population of MM patients.